Cultivation of edible filamentous fungus Aspergillus oryzae on volatile fatty acids derived from anaerobic digestion of food waste and cow manure. (October 2021) - Uwineza, Clarisse; Mahboubi, Amir; Atmowidjojo, Amelia; Ramadhani, Alya; Wainaina, Steven; Millati, Ria; Wikandari, Rachma; Niklasson, Claes; Taherzadeh, Mohammad J.
Graphical abstract: Highlights: Effect of salts supplementation, pH and nitrogen source was investigated on fungal growth on VFAs. The growth of A. oryzae on VFAs was affected by type, concentration and distribution of VFAs. A. oryzae prioritized acetic acid consumption in synthetic and waste-derived VFAs effluents. VFAs derived from AD of cow manure and food waste are promising fungal growth media. Fungal biomass with 37–41% protein content was obtained by growing A. oryzae on waste-derived VFAs. Abstract: In a circular economy approach, edible filamentous fungi (single cell protein) can be cultivated on volatile fatty acids (VFAs) derived from anaerobic digestion (AD) of organic-rich waste streams. In this study, the effect of pH, concentration/distribution of VFAs, nutrient supplementation, and type of waste on Aspergillus oryzae cultivation on synthetic VFAs, and actual VFAs derived from AD of food waste and cow manure were investigated. The optimal pH for A. oryzae growth on VFAs were 6 and 7 with maximum acetic acid consumption rates of 0.09 g/L.h. The fungus could thrive on high concentrations of acetic (up to 9 g/L) yielding 0.29 g dry biomass/gVFAsfed . In mixed VFAs cultures, A. oryzae primarily consumed caproic and acetic acids reaching a biomass yield of 0.26 g dry biomass/gVFAsfed (containing up to 41% protein). For waste-derived VFAs at pH 6, the fungus successfully consumed 81–100% of caproic, acetic, and butyric acids.